Modeling aerosol bolus inhalations in the human lung with the multiple path particle deposition model: Comparison with experimental data - Asgharian, B.; Price, O.; Borojeni, A.A.T.; Kuprat, A.P.; Colby, S.; Singh, R.K.; Corley, R.A.; Darquenne, C. (Journal of aerosol science, 2025)
Existing one-dimensional (1D) models of aerosol dosimetry often ignore mixing mechanisms of inhaled aerosols during their transport in the lung. This mixing or aerosol dispersion results from different physical mechanisms in different regions of the lung. It is a higher order effect, which cannot be directly captured in 1D modeling approaches, and thus is sometimes modeled as a diffusive process. In this study, we improved our recently developed alveolar mixing module incorporated in the multiple path particle dosimetry model (MPPD) to account for flow irreversibility and particle trapping in the alveolar spaces, as well as mixing occurring in the tracheobronchial region. This new version of MPPD was coupled with CFPD-based predictions of aerosol bolus dispersion in the oral airway. The model was used to predict the deposition, dispersion, and mode shift of aerosol bolus inhaled at different penetration depths within the lung for breathing patterns and particle size matching those used in a previous experimental study (Darquenne et al., 2016). Even though a quite simplified approach was used, the computations appear to describe subject-specific and test-specific experimental data reasonably well. The proposed combined dispersion-deposition model can be a useful tool for targeted drug delivery and also for exposure health risk assessment. •Particle dispersion model was included in all regions of the respiratory tract.•Bolus deposition fractions closely matched the measurements from eight subjects.•The predicted bolus half-width closely aligned with the measurements.•Some differences were observed between the predicted and measured mode shift.